2019
DOI: 10.1111/1759-7714.13265
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 as a candidate serological biomarker for the diagnosis of non‐small cell lung cancer: A meta‐analysis

Abstract: Background: To investigate the diagnostic efficacy of long noncoding RNA metastasis-associated in lung adenocarcinoma transcript l (MALAT1) as a candidate serological biomarker for non-small cell lung cancer (NSCLC). Methods: Diagnostic studies relevant to circulation long noncoding RNA MALAT1 as a candidate serological biomarker for NSCLC were electronically systematically searched in PubMed, EMBASE, EBSCO and CNKI databases. Suitable studies were included in the meta-analysis by pooling the diagnostic sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In addition, a lot of data indicate that lncRNAs play an important role in the occurrence and development of cancer [9]. Studies have shown that lncRNA MALAT1 can be used as a biomarker, which is beneficial for the early diagnosis and treatment of the lung cancer [10,11]. LncRNAs also play an important role in the development of serous ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a lot of data indicate that lncRNAs play an important role in the occurrence and development of cancer [9]. Studies have shown that lncRNA MALAT1 can be used as a biomarker, which is beneficial for the early diagnosis and treatment of the lung cancer [10,11]. LncRNAs also play an important role in the development of serous ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…MALAT1 and GAS5 are diagnostic biomarkers for NSCLC. 22,23 LINC00504 and NANCI are also associated with NSCLC prognosis. 24,25 In this study, we found that LINC01089 expression was significantly reduced in LUAD, LUSC, and NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports revealed that lncRNA Metastasis-Associated Lung Adenocarcinoma Transcript 1 (MALAT1) has crucial functions in malignant cancer progression 12 . Extensive evidence has shown that MALAT1 is aberrantly expressed in a broad range of human malignancies, including lung cancer 13 , 14 , pancreatic cancer 15 , 16 , cervical cancer 17 , breast cancer 18 , 19 , osteosarcoma 20 and ESCC 12 . MALAT1 regulates tumor progression by various signaling pathways and mechanisms, particularly EMT 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%